Indonesian Art Education with White Cube Learning Environments as an Inclusive Approach for Multicollaborative Learning - Aruna, Alby; Praherdhiono, Henry; Aulia, Fikri (Universitas Negeri Padang, 2024)
This study aims to explore the potential implementation of White Cube Learning Environments (WCLE) as an inclusive learning method in art education in Indonesia. This research focuses on how WCLE can increase collaboration, creativity, and inclusivity among learners from different backgrounds. This study uses a qualitative descriptive approach. This qualitative analysis helps in understanding the perceptions, effectiveness, and challenges of implementing WCLE in the context of education, art practitioners, and physical galleries as multi-collaborators. The findings of this study provide an alternative contribution that WCLE can be an effective learning tool in supporting a more inclusive and collaborative arts education in Indonesia with the scope of smart learning design despite challenges, such as limited infrastructure and resistance from traditional learning approaches. Recommendations for best practices and further implementation strategies become intact recommendations that offer insights for stakeholders in arts education to adopt and adapt these models according to the needs of efficient learning. Keywords: Written in English. Choosing appropriate keywords is important, because these are used for indexing purposes. Please select a maximum of 5 words to enable your manuscript to be more easily identified and cited.